Solution and Aging of MAR-M246 Nickel-Based Superalloy - Baldan, Renato [UNESP]; da Silva, Antonio Augusto Araújo Pinto; Nunes, Carlos Angelo; Couto, Antonio Augusto; Gabriel, Sinara Borborema; Alkmin, Luciano Braga (Springer Nature, 2017)
Solution and aging heat-treatments play a key role for the application of the superalloys. The aim of this work is to evaluate the microstructure of the MAR-M246 nickel-based superalloy solutioned at 1200 and 1250 °C for 330 min and aged at 780, 880 and 980 °C for 5, 20 and 80 h. The γ′ solvus, solidus and liquidus temperatures were calculated with the aid of the JMatPro software (Ni database). The as-cast and heat-treated samples were characterized by SEM/EDS and SEM-FEG. The γ′ size precipitated in the aged samples was measured and compared with JMatPro simulations. The results have shown that the sample solutioned at 1250 °C for 330 min showed a very homogeneous γ matrix with carbides and cubic γ′ precipitates uniformly distributed. The mean γ′ size of aged samples at 780 and 880 °C for 5, 20 and 80 h did not present significant differences when compared to the solutioned sample. However, a significant increasing in the γ′ particles was observed at 980 °C, evidenced by the large mean size of these particles after 80 h of aging heat-treatment.
Keywords: aging; heat-treatment; MAR-M246; microstructure; solution; superalloy